Decolonisation in universities: The politics of knowledge, edited by Jonathan D. Jansen - Naiefa Rashied (University of Johannesburg, 2021)
In this review of Decolonisation in Universities: The Politics of Knowledge, edited by Jonathan D. Jansen, book reviewer Naiefa Rashied explains how this book serves as an enriching resource for understanding decolonisation from a variety of disciplinary perspectives. This book is an important resource for academics and other stakeholders who are interested in decolonisation, particularly with respect to curriculum reform in higher education.